Vibrational cues enhance believability of ego-motion simulation - Schulte-Pelkum, J.; Riecke, B. E.; Bülthoff, H. H (International Multisensory Research Forum (IMRF), 2004)
We investigated whether the visually induced perception of illusory self-motion (vection) can be influenced by vibrational cues. Circular vection was induced in 22 observers who viewed a naturalistic scene displayed on a projection screen (FOV 54?x40.5?). Two factors were varied: The velocity profile of the visual stimulus (3 or 12 sec to reach 30?/s), and the presence or absence of vibrations. Vibrations were generated by 4 subwoofers mounted below the seat and floor panel. Participants used a joystick to indicate vection onset, and the convincingness of the illusion was rated by magnitude estimation. Data analysis showed that fast accelerations resulted in shorter vection-onset times. Convincingness ratings were affected significantly by the vibrations: With the vibrations, vection was rated to be more convincing. Vection-onset latency, however, was not influenced by vibrations. Interestingly, 3 participants stated that vibrations reduced vection because the vibration amplitudes were not matched to the visual velocity profiles and thus became unrealistic. We conclude that vibrations can influence the convincingness of vection, but that cognition has a moderating effect: If conflicts between visual and vibrational cues are registered, vection seems to be reduces because of the cognitive conflict. These results are relevant for the design of ego-motion simulators. SUPPORT: EU grant POEMS-IST-2001-39223 (see www.poems-project.info) and Max Planck Society.
Keywords: Riecke; Riecke_2004; bernhard-riecke; iSpaceWeb; multi-modal vection; talkWithoutPaper; vection